The Dead Sea scrolls: transmission of traditions and production of texts - Metso, Sarianna (Studies on the texts of the desert of Judah, 2010)
Tradition and innovation in the Dead Sea scrolls Moses trumping Moses : making the book of Jubilees Some translation and copying mistakes from the original Hebrew of the Testaments of the twelve patriarchs Why Nabonidus? Excavating traditions from Qumran, the Hebrew Bible, and neo-Babylonian sources The emergence of Aramaic and Hebrew scholarly texts : transmission and translation of alien wisdom Shared traditions : points of contact between S and D Aspects of the physical and scribal features of some Cave 4 "continuous" pesharim Some thoughts about the diffusion of biblical manuscripts in antiquity Assessing Emanuel Tov's "Qumran scribal practice The evolutionary production and transmission of the scriptural books Beyond the sectarian divide : the "voice of the teacher" as an authority-conferring strategy in some Qumran texts John J. Collins -- James C. VanderKam -- James L. Kugel -- Carol A. Newsom -- Mladen Popović -- Charlotte Hempel -- George J. Brooke -- Emanuel Tov -- Eibert J.C. Tigchelaar -- Eugene Ulrich -- Florentino García Martínez